Effects of Metformin on Ischemia/Reperfusion Injury: New Evidence and Mechanisms - Estefanie Osorio-Llanes; Wendy Villamizar-Villamizar; María Clara Ospino Guerra; Luis Antonio Díaz-Ariza; Sara Camila Castiblanco-Arroyave; Luz Medrano; Daniela Mengual; Ricardo Belón; Jairo Castellar-López; Yanireth Sepúlveda; César Vásquez-Trincado; Aileen Y. Chang; et al. (MDPI AG, 2023)
The search for new drugs with the potential to ensure therapeutic success in the treatment of cardiovascular diseases has become an essential pathway to follow for health organizations and committees around the world. In June 2021, the World Health Organization listed cardiovascular diseases as one of the main causes of death worldwide, representing 32% of them. The most common is coronary artery disease, which causes the death of cardiomyocytes, the cells responsible for cardiac contractility, through ischemia and subsequent reperfusion, which leads to heart failure in the medium and short term. Metformin is one of the most-used drugs for the control of diabetes, which has shown effects beyond the control of hyperglycemia. Some of these effects are mediated by the regulation of cellular energy metabolism, inhibiting apoptosis, reduction of cell death through regulation of autophagy and reduction of mitochondrial dysfunction with further reduction of oxidative stress. This suggests that metformin may attenuate left ventricular dysfunction induced by myocardial ischemia; preclinical and clinical trials have shown promising results, particularly in the setting of acute myocardial infarction. This is a review of the molecular and pharmacological mechanisms of the cardioprotective effects of metformin during myocardial ischemia-reperfusion injury.